School Coexistence in Peruvian Adolescents: A Network Analysis Study - Puma-Maque, Oscar Carlos (2025)
Objective. This study examined the dynamics of school coexistence among Peruvian adolescents using network analysis. Method. The sample consisted of 1083 adolescents who completed the School Coexistence Scale. A psychometric evaluation of the instrument was conducted to ensure its validity and reliability, followed by network analysis to identify the key dimensions of school coexistence. Results. The scale demonstrated appropriate psychometric properties, with Positive Interpersonal Management emerging as the central dimension in the sample. These findings suggest that network analysis provides new insights into school coexistence and highlights some differences in network connectivity by gender, which requires further investigation.